Phage Reduce Stability for Regaining Infectivity during Antagonistic Coevolution with Host Bacterium - Yihui Yuan; Qin Peng; Shaowen Zhang; Tingting Liu; Shuo Yang; Qiuhan Yu; Yan Wu; Meiying Gao (Viruses, 2019)
The coevolution between phage and host bacterium is an important force that drives the evolution of the microbial community, yet the coevolution mechanisms have still not been well analyzed. Here, by analyzing the interaction between a Bacillus phage vB_BthS_BMBphi and its host bacterium, the coevolution mechanisms of the first-generation phage-resistant bacterial mutants and regained-infectivity phage mutants were studied. The phage-resistant bacterial mutants showed several conserved mutations as a potential reason for acquiring phage resistance, including the mutation in flagellum synthesis protein FlhA and cell wall polysaccharide synthesis protein DltC. All the phage-resistant bacterial mutants showed a deleted first transmembrane domain of the flagellum synthesis protein FlhA. Meanwhile, the regain-infectivity phage mutants all contained mutations in three baseplate-associated phage tail proteins by one nucleotide, respectively. A polymorphism analysis of the three mutant nucleotides in the wild-type phage revealed that the mutations existed before the interaction of the phage and the bacterium, while the wild-type phage could not infect the phage-resistant bacterial mutants, which might be because the synchronized mutations of the three nucleotides were essential for regaining infectivity. This study for the first time revealed that the synergism mutation of three phage baseplate-associated proteins were essential for the phages’ regained infectivity. Although the phage mutants regained infectivity, their storage stability was decreased and the infectivity against the phage-resistant bacterial mutants was reduced, suggesting the phage realized the continuation of the species by way of “dying to survive„.